Microsoft 365 Business for admins for dummies - Reed, Jennifer (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
"[G]ain an understanding of Microsoft 365 Business, a complete integrated solution for business productivity and security powered by Office 365, Enterprise Mobility + Security, and Windows 10 [Business]"--Page [4] of cover.
Part 1: Transforming the small business. Understanding the new world of work ; Getting to know Microsoft 365 Business -- Part 2: Implementing Microsoft 365. Preparing for implementation ; Migrating to Office 365 ; Deploying Windows 10 ; Configuring security features ; Getting tactical with the deployment -- Part 3: Driving productivity and collaboration. unlocking enhanced collaboration ; Teaming up digitally -- Part 4: Building a culture of security. Managing passwords ; Configuring multi-factor authentication ; Demystifying information protection ; Measuring your security posture -- Part 5: Managing mobile devices and apps. Introducing Microsoft Intune ; Managing mobile devices ; Managing mobile applications ; Browsing with the Edge mobile app -- Part 6: Administering the service. Working in Microsoft 365 admin center ; Creating reports and alerts ; Managing collaboration workspaces -- Part 7: The part of tens. Ten apps and features an admin should know ; Ten ways to be productive in Microsoft 365 Business ; Ten tips to drive adoption.
Includes index.
Keywords: Microsoft Office; Microsoft Windows (Computer file); Microsoft Office; Microsoft Windows (Computer file); Microsoft software; Cloud computing; Business -- Computer programs; Business -- Computer programs; Cloud computing; Microsoft software